(untitled) (Canadian Medical Education Journal, 2021)
Purpose: An important element in each teaching workshop for resident doctors at the University of Saskatchewan is the microteaching sessions, including feedback. We set out to test our observations that one condition for organizing the feedback increased the quality of feedback. In one condition, residents provide and receive feedback in all areas listed on our feedback form; while in the other condition, they provide and receive feedback in some areas. Methods: Over 115 residents participated in the teaching workshop in the 2019-2020 academic year. Each resident experienced both conditions for giving and receiving feedback—about half with one condition first and the other half in the opposite order. We developed and tested a simple survey that asked about the usefulness of the feedback. Results: We used the Mann-Whitney U test for differences between some areas or all areas. We found a statistically significant difference with small to moderate effect sizes (Cohen’s d) favouring the some areas condition. Conclusion: Residents found the usefulness of feedback given or received using the feedback condition in some areas greater than all areas. We will now only use the some areas condition and recommend that other teaching workshops that use microteaching practice sessions consider using this condition.